Serological markers and risk factors for hepatitis B and C viruses in patients infected with human immunodeficiency virus Marcadores serológicos y factores de riesgo para los virus de la hepatitis B y C en individuos infectados por el VIH - Alvaro Hoyos-Orrego; Mónica Massaro-Ceballos; Marta Ospina-Ospina; Carolina Gómez-Builes; Nora Vanegas-Arroyave; Juan Tobón-Pereira; Javier Jaramillo-Hurtado; María Teresa Rugeles-López (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
Both hepatitis B and hepatitis C viruses (HBV and HCV) infection are common in HIV-infected individuals as a result of shared risk factors for acquisition. A serological study for HBV and HCV was performed in 251 HIV-positive individuals from Medellín, Colombia. A qualitative RT-PCR for HCV was done in 90 patients with CD4+ T-cell count < 150 per mm³. Serological markers for HBV infection were present in 97 (38.6%) patients. Thirty six of them (37.1%) had isolated anti-HBc. A multivariate analysis indicated that the following risk factors were significantly associated with the presence of these markers: age (OR = 1.05, 95% CI: 1.01-1.08), pediculosis pubis (OR = 1.83, 95% CI: 1.01-3.33), men who have sex with men and women (OR = 3.23, 95% CI: 1.46-7.13) and men who have sex only with men (OR = 3.73, 95% CI: 1.58-8.78). The same analysis restricted to women showed syphilis as the only significant risk factor. Thus, HBV infection was considerably associated with high risk sexual behavior. HCV was present in only two (0.8%) of HIV patients. Both of them were positive by RT-PCR and anti-HCV. This low frequency of HIV/HCV coinfection was probably due to the uncommon intravenous drug abuse in this population. The frequent finding of isolated anti-HBc warrants molecular approaches to rule out the presence of cryptic HBV infection. La infección por los virus de la hepatitis B y hepatitis C (VHB y VHC) es frecuente en individuos infectados por el VIH como resultado de compartir factores de riesgo para su contagio. Se realizó un estudio serológico para el VHB y VHC en 251 individuos VIH positivos de la ciudad de Medellín, Colombia. En 90 pacientes con un recuento de linfocitos T < 150 células por mm³ se hizo una PCR-RT cualitativa para el VHC. Se encontraron marcadores serológicos para la infección por el VHB en 97 (38.6%) pacientes. Treinta y seis de 97 (37.1%) tuvieron un anti-HBc aislado. El análisis multivariado indicó que los factores de riesgo significativos asociados a la presencia de estos marcadores fueron: edad (OR = 1.05, 95% IC: 1.01-1.08), pediculosis púbica (OR = 1.83, 95% IC: 1.01-3.33), hombres que tienen sexo con hombres y mujeres (OR = 3.23, 95% IC: 1.46-7.13) y hombres que tienen sexo solo con hombres (OR = 3.73, 95% IC: 1.58-8.78). El mismo análisis restringido a mujeres mostró que la sífilis fue el único factor de riesgo significativo. Por lo tanto, la infección por el VHB fue considerablemente asociada a conductas sexuales de alto riesgo. El VHC se presentó en solo 2 (0.8%) de los pacientes VIH. Ambos pacientes fueron positivos por la PCR-RT y los anti-VHC. La baja frecuencia de la coinfección VIH/VHC fue probablemente debido al bajo uso de drogas intravenosas en esta población. El hallazgo frecuente de anti-HBc como marcador aislado asegura estudios moleculares para descartar la presencia de infección críptica por el VHB.